A global questionnaire survey of the scholarly communication attitudes and behaviours of early career researchers. Issue 3 (30th January 2020) - Nicholas, David; Jamali, Hamid R.; Herman, Eti; Watkinson, Anthony; Abrizah, Abdullah; Rodríguez‐Bravo, Blanca; Boukacem‐Zeghmouri, Cherifa; Xu, Jie; Świgoń, Marzena; Polezhaeva, Tatiana
Abstract : This article describes an international study informed by a 3‐year‐long qualitative longitudinal project, which sought to discover the scholarly communication attitudes and behaviour of early career researchers (ECRs). Using a combination of small‐scale interviews and a larger‐scale survey, ECRs were questioned on their searching and reading behaviour, publishing practices, open data, and their use of social media. Questionnaire invitations were sent out via publisher lists, social media networks, university research networks, and specialist ECR membership organizations. One‐thousand and six‐hundred responses were received, with many coming from China, Russia, and Poland. Results showed that ECRs are adopting millennial‐facing tools/platforms, with Google, Google Scholar, social media, and smartphones becoming embedded in their scholarly activities. Open data sharing obtains widespread support but somewhat less practice. There are some differences in attitudes and behaviour according to age and subject specialism.